Penerapan LKM RUKESA Berbasis Canva untuk Meningkatkan Pemahaman Menulis Deskripsi Murid Kelas IV Sekolah Dasar - Alima, Fayza Chayara; Purwati, Panca Dewi (Lembaga Yasin AlSys, 2025)
Although descriptive writing skills have received considerable attention in previous studies, research that specifically integrates Canva-based student worksheets (Lembar Kerja Murid, LKM) with contextual observation activities remains limited. This study aims to analyze the effectiveness of the Canva-based RUKESA student worksheet in improving fourth-grade elementary students’ understanding of descriptive writing. A mixed-methods approach with an embedded concurrent design was employed, involving 13 fourth-grade students at SDN Pleburan 1 Semarang selected through purposive sampling. Data were collected through pretest–posttest assessments, observations of the learning process, interviews, and documentation. Quantitative data were analyzed using descriptive statistics and N-gain calculations, while qualitative data were analyzed using the Miles and Huberman model. The results show a significant improvement in students’ understanding of descriptive writing, as evidenced by an increase in the mean score from 66 on the pretest to 87 on the posttest, with an N-gain value of 0.65 categorized as medium. Qualitative findings indicate that the Canva-based RUKESA student worksheet enhances students’ activeness, focus, and communication skills during learning activities. This study contributes to strengthening constructivist theory in the context of digital learning and expands understanding of the use of interactive visual media to support writing skills. It underscores the importance of Canva-based media in facilitating more structured and engaging descriptive writing instruction and recommends further research with larger sample sizes and quasi-experimental designs to obtain more comprehensive findings.